Ground Effect on Aerodynamic Characteristics of Flapping-Wing Micro Air Vehicles - Nguyen, Anh-Tuan; Vu, Thanh-Trung; Pham, Thanh-Dong; Dinh, Cong-Truong (Old Journal, 2020)
This paper presents the ground effect on the aerodynamic performance of a hawkmoth-like flapping-wing micro air vehicle. An unsteady aerodynamic model based on the potential-flow theory is used to determine the ground effect at several flight conditions. In this research, the program is written in FORTRAN programming language by using OpenMP library for parallel computing. It was found that the ground effect is the most significant when the flapping-wing micro air vehicle is hovering with a reduction in the lift force when the distance from the center of mass of the flapping-wing micro air vehicle to the ground is below 0.05 m. For forward flight, this effect tends to decrease as the flight speed increases.